Differentiation of Xanthomonas spp. Causing Bacterial Spot in Bulgaria Based on Biolog System - Mariya Stoyanova; Taca Vancheva; Penka Moncheva; Nevena Bogatzevska (International Journal of Microbiology)
During the last 20 years, the causative agents of bacterial spot of tomato and pepper have been subjected to many studies and reclassifications. According to the current data, the species are four (X. euvesicatoria, X. vesicatoria, X. gardneri, and X. perforans) and cause similar symptoms in plants but possess different phenotypic properties. This work provides the full metabolic characteristics obtained by Biolog system of bacterial spot’s xanthomonads based on a large selection of strains from different vegetable-producing regions of Bulgaria with accent on their major differentiating properties which could be used for species differentiation by metabolic profiles. The results are compared to the data available in the literature in order to clarify the strong features of each species and distinguish the variable ones. Simple characteristics like amylase activity and utilization of cis-aconitate cannot serve alone for differentiation.